The sociolinguistic factors that influence the choice of address terms in the Spanish film ‘Roma’ - Mansor, Nor Shahila; Chin, Mooisan (Niu jin da xue zhu ban she, 2022)
This study examined the address terms performed by characters in the Spanish movie ‘Roma’ regarding their functions and the social factors that influence the choice of these address terms. A qualitative approach was used, and the findings were presented in narrative and descriptive forms. The data consisted of the entire interactions in Spanish and were studied using a review method. The study is based on the address term framework established by Kroger et al. (1984). The findings suggest nine address terms used by characters in this film, which are informal second-person singular ‘tú’, formal second-person singular ‘usted’, formal second person plural ‘ustedes’, first name, kinship terms, title plus name, title, pet names, and other expressions. The analysis revealed three main functions: the degree of intimacy, differences in power, and the respect shown amongst interlocutors. The results indicated that several social factors influence the choice of the address terms used, such as the context, social relationships, age, family relationships, and social statuses of the speaker and hearer. The results expand our knowledge in sociolinguistic, pragmatics, and language teaching and learning and provide some insights for the scholars interested in these areas about the Spanish address terms used in literary works and media products. By gathering and sorting out the address terms in this study, it will contribute more empirical data on Spanish address terms. Additionally, the current study is a significant practice that will optimize the classification framework of address terms.